1998
DOI: 10.1002/pro.5560070906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt bridges on protein structure and design

Abstract: Theoretical calculations (Hendsch ZS & Tidor B, 1994, Protein Sci 3:211-226) and experiments (Waldburger CD et al., 1995, Nut Struct Biol 2:122-128;Wimley WC et al., 1996, Proc Natl Acud Sci USA 93:2985-2990) suggest that hydrophobic interactions are more stabilizing than salt bridges in protein folding. The lack of apparent stability benefit for many salt bridges requires an alternative explanation for their occurrence within proteins. To examine the effect of salt bridges on protein structure and stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 70 publications
4
61
0
Order By: Relevance
“…Sequence and structural comparisons between functionally homologous proteins from mesophilic and thermophilic organisms have pointed out that high thermal stability is usually related to multiple factors (8,11,16,17,19,20,25,37,39,41,42,(45)(46)(47)(48). Recently, a series of findings have suggested that thermostability can be also achieved by single ad hoc mutations, possibly allowing the formation of ion pairs or ion networks (26, 44) and/or optimization of long-range coulombic interactions on the protein surface (15,23,36,40).…”
mentioning
confidence: 99%
“…Sequence and structural comparisons between functionally homologous proteins from mesophilic and thermophilic organisms have pointed out that high thermal stability is usually related to multiple factors (8,11,16,17,19,20,25,37,39,41,42,(45)(46)(47)(48). Recently, a series of findings have suggested that thermostability can be also achieved by single ad hoc mutations, possibly allowing the formation of ion pairs or ion networks (26, 44) and/or optimization of long-range coulombic interactions on the protein surface (15,23,36,40).…”
mentioning
confidence: 99%
“…One suggestion from the work is that the replacement of salt bridges with hydrophobic groups of similar size and shape could lead to more stable proteins. A further suggestion advanced is that compensated electrostatic interactions, even if destabilizing, could enhance specificity by dramatically disfavoring arrangements in which polar and charged groups are buried but not compensated~Hendsch & Tidor, 1994;Sindelar et al, 1998!. In an experimental study involving combinatorial mutagenesis of a salt bridge triad in Arc repressor, Waldburger et al~1995! found that simultaneous hydrophobic substitutions for all three members of the salt bridge triad produced stability enhancements in the range of 1-2 teins, respectively, Wimley et al~1996!…”
mentioning
confidence: 99%
“…It only maintains the specific folding of protein, and its functional interactions [33,34]. A simple form of the electrostatic energy, E ES , is given by the distance-attenuated Coulomb interaction term [16],…”
Section: Electrostatic Energymentioning
confidence: 99%